Does consumers’ propensity towards halal organic food purchase matter? Malaysian evidence - Putit, Lennora; Ali, Azrin; Johan, Zaimy Johana; Abdullah, Mohamad Fariz; Ahmad Suki, Amirah (e-International Publishing House, 2025)
Demands for Halal (or permissible) organic products have been increasingly emerging in recent times. This study aims to investigate the consumers’ propensity to purchase halal organic food products in Malaysia. Specifically, it examines whether halal awareness, attitude, social influences, brand trust, product safety, and promotion affect purchase intentions. Using a non-probability sampling technique, 250 online survey questionnaires were distributed to targeted respondents, yielding 200 usable responses. Data were analysed using Smart PLS (version 4.0) statistical software. The findings revealed that attitude and social influence significantly impact consumers’ willingness to purchase halal organic food products. The study further discusses managerial implications